The Dark Triad Personality Traits in Relation to Cyberbullying: The Role of Self-Esteem as a Mediator: [Hubungan Kepribadian Dark Triad dan Cyberbullying: Peran Self-Esteem Sebagai Mediator] - Asih, Sali Rahadi; Lutfiyah (Faculty of Psychology, Universitas Surabaya, 2023)
A cyberbullying study in Indonesia found that 84% of young people aged 12-17 years conducted cyberbullying. The consequences of cyberbullying emphasize the importance of studying the predictors and mechanism of cyberbullying. A number of studies have found that cyberbullying is related to Dark Triad personality traits and self-esteem. Dark Triad personality traits consist of three characteristics, namely the traits of: (1) psychopathy, Machiavellianism, and narcissism. This study aims to see the role of self-esteem as a mediator in the relationship between Dark Triad personality traits and cyberbullying in the age of 20-35 years. Participants of this studi consist of 292 individuals where 70.89% of them are women. This study utilizes three scales, namely cyberbullying scale, Rosenberg Self-Esteem Scale (RSES), and Short Dark Triad Scale (SD3). The result of this study finds that self-esteem mediates traits of psychopathy toward cyberbullying. High self-esteem in individuals with traits of psychopathy results in higher trend in conducting cyberbullying. On the other hand, self-esteem may not significantly mediate between the traits of narcissism and Machiavellianism with cyberbullying. Results of this study aims to provide an implication related to the prevention or intervention of cyberbullying. Sebuah studi cyberbullying di Indonesia menemukan sebanyak 84% anak muda berusia 12-17 tahun melakukan cyberbullying. Konsekuensi dari cyberbullying menekankan pentingnya meneliti prediktor dan mekanisme cyberbullying. Sejumlah studi telah menemukan bahwa cyberbullying terkait dengan kepribadian Dark Triad dan self-esteem. Kepribadian Dark Triad terdiri dari tiga karakteristik, yaitu sifat psikopati, Machiavellianisme, dan narsisisme. Studi ini bertujuan untuk melihat peran self-esteem sebagai mediator dalam hubungan antara kepribadian Dark Triad dan cyberbullying pada usia 20-35 tahun. Partisipan studi terdiri dari 292 individu, dengan 70,89% merupakan perempuan. Studi ini menggunakan tiga alat ukur yaitu skala pengukuran cyberbullying, Rosenberg Self-Esteem Scale (RSES), dan Short Dark Triad Scale (SD3). Hasil studi ini menemukan bahwa self-esteem memediasi sifat psikopati terhadap cyberbullying. Self-esteem yang tinggi pada individu dengan sifat psikopati menghasilkan kecenderungan yang lebih tinggi dalam melakukan cyberbullying. Di sisi lain, self-esteem tidak memediasi secara signifikan antara sifat narsisisme maupun sifat Machiavellianisme dengan cyberbullying. Hasil studi ini diharapkan mampu menyediakan implikasi sehubungan pencegahan atau intervensi cyberbullying.